Ectopic and extranumerary parathyroid glands location in patients with hyperparathyroidism secondary to end stage renal disease - Gomes,Elaine Maria Santos (2007)
Supranumerary or ectopic parathyroid glands are the main cause of persistent hyperparathyroidism (HPT) in patients with end stage renal disease (ESRD) submitted to parathyroidectomy (PTx). PURPOSE: To evaluate the prevalence and location of parathyroid glands in these patients. METHODS: Thirty-five patients with ESRD and severe secondary hyperparathyroidism (HPT2) had been submitted to total PTx at HUCFF from December 2001 to July 2005. Surgery was always performed by the same surgeon, who described in details the location of the glands. RESULTS: Sixteen patients (45.7%) had ectopic glands, which were also extranumerary in five of them (14.3%). The most common locations were the thyroid parenchyma (33.3%), thyroid-thymus conduit (18.5%), and thymus (14.8%). Before PTx, the sensibility of ultrasonography and scintigraphy with technetium-99m Sestamibi was low (48.3% and 35.3%, respectively). Moreover, 51.4% of the nodules found at US were thyroid nodules. However, 99mTc-Sestamibi was useful to identify ectopic glands in those two patients with persistent HPT after PTx. CONCLUSION: The presence of extranumerary and ectopic parathyroid glands in HPT2 is sufficiently important to justify their exhaustive search. As the preoperative image exams present low sensibility to locate them, it is necessary to develop an exploratory routine embracing the most common sites of location.